A Comprehensive Review of Cymbopogon Using Herbarium Specimens from India - Murugan Manisha,; Subramani Vijay Sharma,; Perumal Ravichandran, (The Bioscan, 2026)
Herbarium specimens serve as foundational resources for systematic, ecological, and evolutionary studies, providing verifiable records for plant diversity and nomenclature. This study examined 738 herbarium specimens of the genus Cymbopogon collected from 36 Indian and international herbaria, including 165 type specimens. The main objectives were to evaluate species diversity, identify dominant and underrepresented taxa, and assess the role and completeness of type specimen documentation. The results indicate that C. caesius (97 specimens) and C. flexuosus (89 specimens) are the most widely represented species, whereas C. pendulus, C. commutatus, and C. winterianus remain poorly defined. Type specimen assessment revealed significant variation in documentation across taxa, underscoring the need for lectotypification in several underrepresented species. Continental distribution analysis showed that Asian herbaria contribute the largest number of collections, followed by Europe and North America. Despite the rich historical record, 55% of specimens lacked geospatial data and 9% lacked collection dates, highlighting persistent metadata gaps. This work demonstrates the enduring value of herbarium collections as repositories for taxonomic clarification, biodiversity documentation, and conservation planning, while emphasizing the importance of integrating molecular and digital resources for future taxonomic refinement of Cymbopogon.